1996
DOI: 10.1080/10473289.1996.10467550
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ethanol-Blended Fuels on the Emissions from Three Pre-1985 Light-Duty Passenger Vehicles

Abstract: Tailpipe and evaporative emissions from three pre-1985 passenger motor vehicles operating on an ethanol oxygenated and on a nonoxygenated (base) fuel were characterized. Emission data were collected for vehicles operating over the Federal Test Procedure at 90 °F, 75 °F, and 40 °F to simulate ambient driving conditions. The two fuels tested were a commercial summer-grade regular gasoline (the nonoxygenated base fuel) and an oxygenated fuel containing 8.8% ethanol, more paraffins and olefins, and less aromatics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 6 publications
1
19
0
2
Order By: Relevance
“…Pollutant formation is an important concern when developing engines for biofuels. NOx, UHC, particulate matter (PM), soot and CO are all important emissions from biofuels, similar to traditional fuels 8 , but there are also elevated levels of oxygenated intermediates like CH2O in biofuel exhaust 3,9,10 . CH2O is carcinogenic and produce ground-level ozone 3,[11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Pollutant formation is an important concern when developing engines for biofuels. NOx, UHC, particulate matter (PM), soot and CO are all important emissions from biofuels, similar to traditional fuels 8 , but there are also elevated levels of oxygenated intermediates like CH2O in biofuel exhaust 3,9,10 . CH2O is carcinogenic and produce ground-level ozone 3,[11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…When ethanol and methanol containing oxygen is blended with gasoline, the combustion of the engine becomes better and therefore CO emission is reduced (Stump et al, 1996;Yasar, 2010). As seen in Fig.…”
Section: Engine Emission Characteristicsmentioning
confidence: 99%
“…6 However, in cases where engine and ignition advance are not modified, it is reported by Dai et al 19 and Li et al 13 who compared ethanol and gasoline and by Costa et al 12 who compared ethanol and ethanol-gasoline mixture in their studies that ethanol causes lower THC and CO, higher NO x emission. In study of Stump et al 20 who performed tests on different vehicles at cruise cycles, it is found that HC and CO emissions decrease with ethanol addition while NO x emissions mostly increase. NO x , THC, and CO emission results in study are parallel with results of Schifter et al 8 Table 5 summarizes the effects of ethanol content of fuel on performance and emission characteristics, which are obtained from simulation results.…”
Section: Emissionsmentioning
confidence: 99%